Effect of plasma ion etching on Si nano wires towards superhydrophobicity. (2016) - Madhavi, K.; Suvarna, P.; Ghosh, M.; Shaik, H.; Mohan Rao, G.
Abstract: Superhydrophobic surfaces have attracted due to their potential applications such as self-cleaning surfaces etc. Many techniques have demonstrated in fabricating the artificial superhydrophobic surfaces such as CVD, Organic coatings etc. In this paper we present simple approach to fabricate non wettable superhydrobic surface on silicon Nanowires (Si NW) surface by H2 ion etching technique through ECR device which is very efficient in producing the high ion density plasma at low pressure and at moderate energy. Large area high density (Si NW) were fabricated by two step Metal assisted chemical etching (MACE)of silicon using silver(Ag) as the catalyst along with pre immersion method.H2 Plasma ion etching treatment was applied on the surface of the SiNW at the constant microwave power. The morphology of Si NWs is changed with the application of plasma which was revealed by Scanning electron microscopy. Water contact angles have been systematically measured for SiNWs&H2 plasma treated SiNWs by increasing the etching time. It was observed that in H2 ion plasma treated SiNWs, the water contact angle changed dramatically from 22.6 0 to 146 0 almost near to super hydrophobic nature. And these result suggest that the hydrogen plasma condition must be carefully regulated to achieve the superhydrophobic surface on silicon which is essential for many applications like Biosensors and Microfluidic surfaces.